(untitled) (Journal of Engineering, 2014)
Test results of six half-scale reinforced concrete flat plates connections with an opening in the vicinity of the column are reported. The test specimens represent a portion of a slab bounded by the lines of contraflexure around the column. The tests were designed to study the effect of openings on the punching shear behavior of the slab-column connections. The test parameters were the location and the size of the openings. One specimen had no opening and the remaining five had various arrangements of openings around the column. All specimens were cast with normal density concrete of approximately 30 MPa compressive strength. The openings in the specimens were square, with the sides parallel to the sides of the column. Three sizes of openings were used: the same size as the column (150 x 150 mm), 67 percent of the column size (100 x 100mm), and 150 percent of the column size (225×225mm). Due to the presence of the openings, the specimens showed a decrease in punching shear capacity ranged between 11.43% and 29.25% with respect to the control solid slab. Also, the stiffness decreased between 0.31% and 83.00%, depending on the size and location of these openings with respect to the column.